2022
DOI: 10.21203/rs.3.rs-1727189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of the An Abbreviated Version of the Mindful Eating Questionnaire in Turkish Adults

Abstract: Purpose: To adapt and validate the an abbreviated version of the Mindful Eating Questionnaire (MEQ-18) to the Turkish language for a Turkish adult population.Methods: This cross-sectional study included 709 participants aged between 18-65 years living in the province of Elazig. The data was collected through a voluntary face-to-face survey. The questionnaire was included their general characteristics and the MEQ-18 and Eating Attitude Test-26 (EAT-26). Confirmatory factor analysis (CFA) was used to test the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The scale is scored between 25 and 125 points. The Cronbach's alpha internal consistency coefficient of the CTQ-SF is 0.77 (Kaya, 2014). In this study, the Cronbach's alpha value of the CTQ-SF was found to be 0.81.…”
Section: Data Collectionmentioning
confidence: 53%
See 1 more Smart Citation
“…The scale is scored between 25 and 125 points. The Cronbach's alpha internal consistency coefficient of the CTQ-SF is 0.77 (Kaya, 2014). In this study, the Cronbach's alpha value of the CTQ-SF was found to be 0.81.…”
Section: Data Collectionmentioning
confidence: 53%
“…Childhood Trauma Questionnaire Short Form (CTQ-SF): This was developed by Bernstein et al (2003) and the validity and reliability of its Turkish version was tested by Kaya (2014). The CTQ-SF is a measurement tool for retrospectively examining the history of neglect and abuse in childhood.…”
Section: Data Collectionmentioning
confidence: 99%